Analyzing the Impact of Brand Equity and Marketing Mix towards Consumer Loyalty: Case Study of Aqua in Surabaya - Christian Adi Basuki (iBuss Management, 2015)
This research is being done to know the impact of brand equity and marketing mix towards consumer loyalty of Aqua in Surabaya. The data was gathered using simple random sampling by distributing o n l i n e questionnaires to 130 respondents in Surabaya. The data was analyzed using Multiple Linear Regression Analysis. The result shows that the brand equity and marketing mix simultaneously have significant impact on consumer loyalty of Aqua in Surabaya. Meanwhile, as individual dimension, brand loyalty, brand awareness, perceived quality, price, and promotion have significant impact toward consumer loyalty of Aqua in Surabaya.Keywords: marketing, consumer behavior, brand equity, marketing mix, consumer loyalty